ANALISIS SISTEM INFORMASI AKUNTANSI PEMBAYARAN TAGIHAN PADA BADAN USAHA MILIK DESA TUMANG CEPOGO, KELURAHAN CEPOGO, KECAMATAN CEPOGO, KABUPATEN BOYOLALI - Triatmaja, Nur Asih; Hapsari, Ferawati Dewi; Theorupun, Milka Susana (Universitas Boyolali, 2023)
Payment of bills in cash is the main activity of the Tumang Cepogo Business Entity. Recording of transactions that are still done manually can result in errors, waste of time and messy recording, so a computerized accounting information system design is needed that can assist in organizing financial functions. This study aims to update financial reports in real time using the Microsoft Access 2020 application. The types of data used are primary data with observations and interviews as well as secondary data in the form of documents, notes and reports. The research results from the database application are in the form of comprehensive reports and financial position reports that are realtime and can be transferred to Microsoft Excel.